2015
DOI: 10.1017/s1092852915000553
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-emergent sexual dysfunction in randomized trials of vortioxetine for major depressive disorder or generalized anxiety disorder: a pooled analysis

Abstract: Objective. Antidepressants are frequently associated with treatment-emergent sexual dysfunction (TESD). Vortioxetine, which was approved for patients with major depressive disorder (MDD), has a receptor profile that suggests limited impact on sexual functioning.Methods. Arizona Sexual Experiences Scale (ASEX) patient-level data were pooled from 7 short-term vortioxetine trials (6 in MDD, 1 in generalized anxiety disorder) and analyzed for incidence of TESD at any post-baseline visit in patients without sexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 26 publications
4
32
0
3
Order By: Relevance
“…Consideration may be given to use of bupropion or buspirone as adjunctive agents for antidepressantinduced sexual dysfunction or as primary pharmacotherapy for anxiety or depression, if appropriate, to help minimize or avoid development of sexual dysfunction. Vortioxetine [34] and vilazodone [35,36] are newer antidepressants that appear to have a lower incidence of sexual dysfunction associated with use and should be considered in treating patients with depression and anxiety who have experienced sexual dysfunction with other antidepressant medications.…”
Section: Interventions For Treatment-emergent Sexual Dysfunction Withmentioning
confidence: 99%
“…Consideration may be given to use of bupropion or buspirone as adjunctive agents for antidepressantinduced sexual dysfunction or as primary pharmacotherapy for anxiety or depression, if appropriate, to help minimize or avoid development of sexual dysfunction. Vortioxetine [34] and vilazodone [35,36] are newer antidepressants that appear to have a lower incidence of sexual dysfunction associated with use and should be considered in treating patients with depression and anxiety who have experienced sexual dysfunction with other antidepressant medications.…”
Section: Interventions For Treatment-emergent Sexual Dysfunction Withmentioning
confidence: 99%
“…19 The reported prevalence of sexual dysfunction in several shortand long-term studies in MDD patients treated with vortioxetine indicates that the incidence of TESD was generally similar to that with placebo at 5 and 10 mg and higher than with placebo at 20 mg. 20e27 Similarly, a post hoc pooled analysis that included a non-inferiority margin from the vortioxetine studies demonstrated that low doses of vortioxetine (5 mg) have minor effects on sexual function that are at the placebo level; although a dosedependent increase in the risk of TESD was observed with higher doses (10e20 mg), it was not significantly different from placebo. 28,29 The study presented here aimed to replicate the superior effect of vortioxetine compared with an SSRI on TESD and was conducted in healthy men and women to mitigate the confounding effect of MDD or other medical conditions on sexual functioning. Therefore, this study evaluated the effects on sexual functioning of vortioxetine (10 and 20 mg) compared with paroxetine, an SSRI known to cause sexual dysfunction, and placebo after 5 weeks of treatment in healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…The doses of vortioxetine were selected because they are within the Food and Drug Administration (FDA)-approved efficacious dose range. 28,29…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the difference between the use of spontaneous reports versus a validated questionnaire has already been investigated in patients using vortioxetine by Jacobsen et al (2015b). In a pooled analysis of six MDD studies and one GAD study, all of which were also included in the review of Baldwin et al, TESD was reported spontaneously in 2.2% of vortioxetine-treated patients.…”
Section: To the Editorsmentioning
confidence: 99%
“…Although the incidence of TESD increased with vortioxetine dose there was no statistically significant higher risk of developing TESD versus placebo. Higher TESD risk was reported for duloxetine 60 mg/ day versus placebo and versus vortioxetine 5 or 10 mg while no significant difference was determined between duloxetine 60 mg/day versus vortioxetine 15 or 20 mg.When comparing the papers of Baldwin et al (2016) and Jacobsen et al (2015b) that partially describe the same original studies, it again becomes clear that TESD is reported far more frequently when using a validated questionnaire versus spontaneous reports. Only reporting spontaneously mentioned sexual side effects may be less helpful for clinicians who together with their patients choose between different antidepressants based on side effect profiles reported in the literature.…”
mentioning
confidence: 95%